Creature features: The lively narratives of bacteriophages in Soviet biology and medicine. (20th December 2020) - Myelnikov, Dmitriy
Abstract : The term 'bacteriophage' (devourer of bacteria) was coined by Félix d'Herelle in 1917 to describe both the phenomenon of spontaneous destruction of bacterial cultures and an agent responsible. Debates about the nature of bacteriophages raged in the 1920s and 1930s, and there were extensive attempts to use the phenomenon to fight infections. Whereas it eventually became a crucial tool for molecular biology, therapeutic uses of 'phage' declined sharply in the West after World War II, but persisted in the Soviet Union, particularly Georgia. Increasingly isolated from Western medical research, Soviet scientists developed their own metaphors of 'phage', its nature and action, and communicated them to their peers, medical professionals, and potential patients. In this article, I explore four kinds of narrative that shaped Soviet phage research: the mystique of bacteriophages in the 1920s and 1930s; animated accounts and military metaphors in the 1940s; Lysenkoist notions on bacteriophages as a phase in bacterial development; and the retrospective allocation of credit for the discovery of the bacteriophage during the Cold War. Whereas viruses have been largely seen as barely living, phage narratives consistently featured heroic liveliness or 'animacy', which framed the growing consensus on its viral nature. Post-war narratives, shaped by the Lysenkoist movement and the campaigns against adulation of the West, had political power—although many microbiologists remained sceptical, they had to frame their critique within the correct language if they wanted to be published. The dramatic story of bacteriophage research in the Soviet Union is a reminder of the extent to which scientific narratives can be shaped by politics, but it also highlights the diversity of strategies and alternative interpretations possible within those constraints.